Catechol modified quaternized chitosan enhanced wet adhesive and antibacterial properties of injectable thermo-sensitive hydrogel for wound healing. (1st December 2020) - Zheng, Zhiqiang; Bian, Shaoquan; Li, Zhiqiang; Zhang, Zhiyang; Liu, Yuan; Zhai, Xinyun; Pan, Haobo; Zhao, Xiaoli
Graphical abstract: Highlights: Catechol modified quaternized chitosan (QCS-C) was fabricated by functionalization of QCS with catechol group. The QCS-C endowed thermo-sensitive hydrogel with the dual function of antibacterial and wet tissue-adhesive. QCS-C lowered the sol-gel transition temperature of hydrogel for easy gelation. Mice partial laceration model showed this hydrogel could effectively seal the ruptured skin and accelerate wound healing. Abstract: Wound dressings based on injectable thermo-sensitive hydrogel possess several advantages over preformed conventional dressings such as rapid reversible sol-gel transition behavior and the capacity of filling the irregular wound defect. Nevertheless, its clinical application is hindered by the weak tissue adhesiveness. Therefore, in this study, the catechol modified quaternized chitosan (QCS-C) was fabricated and incorporated into poly(d, l-lactide)-poly(ethylene glycol)-poly(d, l-lactide) (PLEL) hydrogel to develop an injectable hydrogel with the properties of thermo-sensitive, antibacterial and tissue adhesive. QCS-C could lower the LCST of hydrogel for easy gelation at physiological temperature, and significantly enhanced the tissue adhesion. For wound generation, nano-scaled bioactive glass (nBG：80 SiO2, 16 CaO and 4 P2 O5 ; mol%) was loaded into hydrogel to promote angiogenesis. The mice partial laceration experiment showed that PLEL-nBG-QCS-C hydrogel could effectively seal the ruptured skin and significantly accelerate wound healing. Thus, our findings established a new type of clinical treatment technology for complicated wounds.